An investigation on the effect of soil erosion on the properties of soil adjacent to a road right of way (ROW) - Abuye Boja; Merihun Tafesse; Sisay Alemu; Tarekegn Shumetie; Eyerusalem Tekeba (Geology, Ecology, and Landscapes)
Recently, soil erosion has been a significant and common issue along road right of way (ROW). This study was designed to identify the effect of soil erosion on the physical and chemical properties of soil across a ROW. Land use land cover (LULC) map, soil map, and field observation were adopted to ensure proper sampling. Moisture content, grain size analysis, soil texture, consistency test, organic content and matter, pH, and cation exchange capacity (CEC) were conducted on 10 representative soil samples collected from 14 km ROW. The laboratory results from moisture content, pH, and CEC revealed samples taken from the erosion fields (20.79% to 26.41%), (8.48 to 8.66), and (18.02 to 24.03) appeared to be higher than those taken from non-eroded fields (16.79% to 18.51%), (8.18 to 8.3), and (14.5 to 16.15), respectively. The organic content of the soil in the non-eroded areas was higher than that in the eroded areas. This variation in soil properties is primarily attributed to differences in LULC and soil composition. With regard to consistency properties, the soil was marked as highly erodible. Treatment of drainage structures, demarcating ROW, ROW stabilization, and awareness creation were proposed as feasible remedial measures. Finally, the soil along Sawla to Bulki ROW was identified as erodible soil as per experimental results and analysis.